SARS-CoV-2 vaccine: current biological targets and considerations - Garcia-Sastre, Adolfo (Henry Stewart Talks, 2020)
Comparison of SARS-COV-2 with other coronavirus strains, Targets for a SARS-COV-2 vaccine, Other considerations once a vaccine has been developed